(3QSGdI GdCYPGQ hGdEfPGQ GdTGajI dbdhH Cgd GdMb ef GdeQVi hGdGNJjGQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG GdMGce HPGJg GdefaQO Yf eHOYGJg ef gGOi GdCeI hfPjQgG s
(3BNQgG (B:s
(3hGbJd GdeTQcjf hGdeQJOjf HSja ehdGfG GdMGce Edg GdYGdejf hHGQF GdNdGFb CLeYjf aGage hUjJi hdGRehG MOhOi JeJ HMeO ehdGfG hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B35s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds